Establishing Prairie Dropseed in Restored Prairies - Brewer, Katherine (My University, 2021)
Integrated plant conservation is the concept of creating a cyclical relationship between in situ and ex situ conservation through propagule collection and restoration. We take an integrated plant conservation approach to understanding the North American native prairie grass, prairie dropseed (Sporobolus heterolepis (A Gray) Gray). Prairie dropseed is a critical prairie species but little is known about its status in Minnesota. Here we provide tools for understanding the distribution and rarity of prairie dropseed across Minnesota through the combined use of databases and Geographic Information Systems (GIS). This allows for efficient and cost effective collection of propagules for ex situ conservation. We also address the need for practical methods for in situ conservation of prairie dropseed, by evaluating two methods for increasing the survival and growth of plugs of prairie dropseed planted in restored prairies. We examine the effectiveness of growing plugs in native soils verses a standard potting mix on seedling survival and growth and the effectiveness of a hydrogel treatment on seedling survival and growth. Plugs grown in potting mix had increased growth rates over plugs grown in native field soil, but soil medium did not affect plug survival. Treating plugs with hydrogel did not increase plug survival or growth.
University of Minnesota M.S. thesis. September 2021. Major: Applied Plant Sciences. Advisor: Mary Meyer. 1 computer file (PDF); vii, 67 pages.